Predictors of medium- and long-term mortality in elderly patients with acute pulmonary embolism - Hernan Polo Friz; Annalisa Orenti; Elia Gelfi; Elena Motto; Laura Primitz; Luca Cavalieri d’Oro; Cristina Giannattasio; Giuseppe Vighi; Claudio Cimminiello; Patrizia Boracchi (Heliyon, 2020)
Introduction: Data on medium- and long-term prognostic factors for death in elderly patients with acute Pulmonary Embolism (APE) are lacking. The present study aimed to assess sPESI score and the Charlson Comorbidity Index (CCI) as medium- and long-term predictors of mortality in elderly patients with haemodinamically stable APE. Methods: All consecutive patients aged≥65 years old, evaluated at the emergency department (ED) of our hospital from 2010 through 2014, with a final diagnosis of APE, were included in this retrospective cohort study. Results: Study population:162 patients, female:36.5%, median age:79 years old, 74% presented a sPESI score>0, and 61% a CCI≥ 1. All causes mortality: 19.8%, 23.5%, 26.5%, 32.1% and 48.2% at 3, 6 months, 1, 2 and 5 years after APE. Univariate regression analysis: CCI≥1 was associated with a higher mortality at 3, 6 months, 1, 2 and 5 years. Multivariate Cox analysis: CCI≥1 associated with increased mortality at 3 months (HR:4.29; IC95%:1.46–12.59), 6 months (HR:5.33; IC95%:1.84–15.44), 1 year (HR:4.87; IC95%:1.87–12.70), 2 years (HR:3.78; IC95%:1.74–8.25), and 5 years (HR:2.30; IC95%:1.33–3.99). sPESI score≥1 was not found to be related to an increased medium-or long-term mortality. Negative predictive values (IC95%) of CCI≥1 were 93.65% (87.61–99.69), 93.65% (87.61–99.69), 92.06% (85.37–98.76), 87.3% (79.05–95.55) and 71.61% (60.13–83.1) for mortality at 3, 6 months, 1, 2 and 5 years. Conclusion: In elderly patients with a confirmed normotensive APE, unlike sPESI score, CCI showed to be an independent prognostic factor for medium- and long-term mortality. In these patients, after the acute phase following a PE event, the assessment of the comorbidities burden represents the most appropriate approach for predicting medium- and long-term mortality.